Measurement of food literacy among the adult population in urban Uganda and Kenya: development and validation of an East African food literacy scale - Peter Yiga; Moses Mokaya; Tonny Kiyimba; Patrick Ogwok; Florence Kyallo; Janna Lena Koole; Tessy Boedt; Christophe Matthys (Cambridge University Press, 2024)
Abstract Objective: Food literacy (FL) is a potential approach to address the nutrition transition in Africa, but a validated tool is lacking. We developed and validated a scale to assess FL among Ugandan and Kenyan adult populations. Design: A mixed-method approach was applied: (1) item development using literature, expert and target group insights, (2) independent country-specific validation (content, construct, criterion and concurrent) and (3) synchronisation of the two country-specific FL-scales. Construct validity was evaluated against the prime dietary quality score (PDQS) and healthy eating self-efficacy scale (HEWSE). Setting: Urban Uganda and Kenya. Participants: Two cross-sectional cross-country surveys, adults >18 years (n = 214) and university students (n = 163), were conducted. Results: The initial development yielded a forty-eight-item FL-scale draft. In total, twenty-six items were reframed to fit the country contexts. Six items differed content-wise across the two FL-scales and were dropped for a synchronised East African FL-scale. Weighted kappa tests revealed no deviations in individuals' FL when either the East African FL-scale or the country-specific FL-scales are used; 0·86 (95 % CI: 0·83, 0·89), Uganda and 0·86 (95 % CI: 0·84, 0·88), Kenya. The FL-scale showed good reliability (0·71 (95 % CI: 0·60, 0·79), Uganda; 0·78 (95 % CI: 0·69, 0·84), Kenya) and positively correlated with PDQS (r = 0·29 P = 0·003, Uganda; r = 0·26 P < 0·001, Kenya) and HEWSE (r = 0·32 P < 0·001, Uganda; r = 0·23, P = 0·017, Kenya). The FL-scale distinguishes populations with higher from those with lower FL (β = 14·54 (95 % CI: 10·27, 18·81), Uganda; β = 18·79 (95 % CI: 13·92, 23·68), Kenya). Conclusion: Provided culture-sensitive translation and adaptation are done, the scale may be used as a basis across East Africa.